SUATU KAJIAN TEORITIS TENTANG PENERJEMAHAN DAN IKLAN - Narius, Don (English Department FBS UNP, 2009)
Translating of a text needs enough skill and knowledge about the topic that will be translated. The meaning including in various language sources, lexical meaning, grammatical meaning, contextual or situational meaning, textual meaning, sociocultural meaning and idiomatic meaning. If it is connected to advertisement, meaning that will be delivered to listener or reader are messages that will persuade the reader for acting. Advertisement language is simple but it has persuasive function. The various advertisement forms have specific challenge in translating, because audio advertisement is different from visual and audio visual. Key words/ phrases: translating, advertisement, meaning, advertisement types